Factoring instytucją współczesnego finansowania działalności gospodarczej - Koćwin, Julitta (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The goal of this article is to present one of the external financing forms of the business, that is factoring, which becomes more and more attractive instrument supporting financial liquidity. To confirm the above thesis, there are drawings, tables and charts presented to picture the dynamics of the use of that financial instrument in Poland at the turn of XX and XXI centuries. This article presents the origins, the definition, the function and the basic types of factoring, as well as its legal regulations, with the particular emphasis on the fact that it is subject to taxation as opposed to the other financial services. Using factoring brings many profits to the entrepreneur, where the most important one is the opportunity to receive funds for delivered goods or completed services without the need to wait until the date of the invoices payment. In the result, the company can increase the production and turnover without involving its own capital. It increases financial liquidity. The other financial indicators improve as well, including the receivables turnover cycle. It creates positive company image amongst suppliers, banks and shareholders
Keywords: factoring; financial instruments; external financing